A new risk-based inspection methodology for offshore floating structures - Ozguc, Ozgur (Informa UK Limited, 2018)
ABSTRACTThe Risk-Based Inspection (RBI) programme is a part of the overall Asset Integrity Management (AIM). The RBI programme offers benefits such as providing a rational basis for inspection plan...